(untitled) (Conference on English Language Teaching, 2025)
This research was aimed to find out the types of authentic materials and analyse the authentic principles of authentic materials in English Indonesian textbook entitled Bahasa Inggris Work in Progress. This research used content analysis with the quantitative descriptive method. The instrument consisted of input authenticity purposed by Nunan and criteria of authenticity by Tomlison which have been validated by the expert. The results showed that there are 3 types of authentic materials were discovered in spoken language and written language. Those authentic materials are authentic listening/viewing material, authentic visual material and authentic printed material. Moreover, the number of authentic materials in written language are more rather than the number of authentic materials in spoken language which consisted of 8 authentic materials in spoken language and 14 authentic materials in written language. Based on the analysis result, the average percentage of authentic principles in spoken language are 51%. This fulfilment indicated that the authentic principles of spoken language in this textbook was “sufficient” category. Furthermore, the average percentage of the authentic principles in written language reached 61%, so that it categorized as the “fair” category.